Patient Monitor for SpO2 and Temperature Parameters - Triwiyanto; Torib Hamzah; Moch Sahrul Triandi Putra Sahrul (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2019)
Patient monitor is an apparatus used to monitor the patient's condition in real-time, hence the patient's physiological conditions can be identified at that time. The purpose of this study is to design a patient monitor for SpO2 and temperature parameters based on computer with Delphi progaming. In this work, the author developed patient monitor with two parameters (SpO2 and Temperature). The workings of this tool are very simple by installing the finger sensor on the finger and the temperature sensor in the armpit area will then be detected by the two sensors that will be displayed on the PC and LCD Characters, analog data from the ADC Atmega is received by the personal computer (PC) via Bluetooth HC -05 and values ​​per parameter are also displayed on the Character LCD. After measuring, get an error in the tool, the biggest SpO2 error of this tool is 1.02% and get the smallest error of 0.8%. And for the biggest error of Temperature of 1.02% and the smallest error of 0.8%.